Developing Project-Based English Learning Activities to Enhance Students’ Learning Engagement in Class IX - Aryaningsih, Ni Putu Ayu; Nitiasih, Putu Kerti; Adnyayanti, Ni Luh Putu Era (Innovative: Journal Of Social Science Research, 2025)
This study aims to enhance students' engagement through the development of English learning activities using project-based learning method for grade IX students at SMPN 5 Singaraja. Based on preliminary data students' engagement was low: 73% cognitive, 87% emotional, and 64% behavioural. This research used the ADDE (Analysis, Design, Development, Evaluation) method, to produce a prototype. As a result, project-based activities were effective in increasing student engagement through relevant tasks, collaboration, and critical thinking. This research provides a practical contribution for teachers in providing innovative learning and impact on students' engagement in English language learning at junior high school level.